2019
DOI: 10.3390/su11205582
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Double-Stage Energy Harvesting Floor Tile

Abstract: This paper introduces the design and characterization of a double-stage energy harvesting floor tile that uses a piezoelectric cantilever to generate electricity from human footsteps. A frequency up-conversion principle, in the form of an overshooting piezoelectric cantilever, plucked with a proof mass is utilized to increase energy conversion efficiency. The overshoot of the proof mass is implemented by a mechanical impact between a moving cover plate and a stopper to prevent damage to the plucked piezoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…For calculating the total energy harvested , the equation was Equation (2), where was the total time while the triboelectric was working was the voltage across the resistive load at a time and was the sampling time interval. We used these equations in the same way that they were used in [ 12 , 13 ]: and …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For calculating the total energy harvested , the equation was Equation (2), where was the total time while the triboelectric was working was the voltage across the resistive load at a time and was the sampling time interval. We used these equations in the same way that they were used in [ 12 , 13 ]: and …”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the second type of test bench had a simple structure and a higher electrical performance than the first type because electrical energy was generated each time the cover plate was pressed and each time it was released. In another study, Don Isarakorn et al [ 13 ] investigated the behavior of double-stage energy harvesting floor tile. They varied the excitation acceleration and gap width of the cover plate, observed the results, and found that the accelerations of the moving cover plate and gap width were directly proportional to the electrical output.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the gap steadily increases the energy output, but a larger gap can make walking on the tiles too uncomfortable. Hence, the gap width should be optimized between high energy generation and comfortable walking [ 109 ]. The buoy is an aerologic device that is restricted to heave motion only.…”
Section: Discussion and Critical Reviewsmentioning
confidence: 99%
“…Hence, the gap width should be optimized between high energy generation and comfortable walking [109]. 4.…”
mentioning
confidence: 99%
“…The optimal value for load resistance can be determined by trying out a range of values for load resistance R L and picking the one that provides the maximum power transfer or extrapolating to the best value from the value that provided the maximum power transfer in the try-out. Equivalently, we can determine a range of values for the internal resistance R int from the achieved maximum or near maximum power transfer by varying the values of the load resistance R L and use a value (exact or extrapolated) in the range to determine the optimal load resistance [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%